EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MASA PANDEMI - Santimina Zebua; Tantri Yulia; Fianus Tandiongan (JOURNAL of THEOLOGICAL STUDENTS, 2022)
AbstractThere is an allegation that the discovery learning model in faith lessons at the sixth grade in Daniel Creative School Semarang has not been maximized.Â  This is because most students are still unable to solve existing problems, are less actively involved and open themselves to new things that were not known before. This study aims to determine the effectiveness of the discovery learning model in learning faith (Christian religion lessons) during the pandemic. The methodology used is descriptive quantitative.Â  Based on the hypothesis test, it was found that the level of effectiveness of the discovery learning model in faith lessons at the sixth grade in Daniel Creative School Semarang was in the good category, namely 79.3%.